Analisis Laporan Arus Kas dalam Mengukur Likuiditas Perusahaan: Studi Kasus pada PT. Unilever Indonesia Tbk Periode 2020 - 2023 - Agung Joni Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
In facing an increasingly competitive market, companies are required to always optimally manage their finances, one of which is through the preparation of transparent financial reports. The cash flow report is included in one of the components of the financial report, presenting detailed information about the company's cash condition generated from operating, investment and financing activities. This study measures liquidity by the ratio of cash flow to current liabilities. In this study, a case study approach was used with a quantitative method. The data used in the analysis are secondary data from the quarterly financial reports of PT. Unilever Indonesia Tbk for 2020 - 2023 obtained through the company's official website. Data was collected using the documentation method. Cash flow ratio analysis techniques and regression analysis were used to analyze the data in this study. Based on the results of the analysis, cash flow from operating activities has a positive and significant effect on the company's liquidity, cash flow from financing activities has a negative and significant effect, while investment cash flow does not have a significant effect. The R Square value of 0.957 indicates that 96% of the company's liquidity can be explained by three cash flow components. The results of this study underline the importance of cash flow management, especially operational activities in maintaining cash stability to pay off short-term liabilities sustainably.